Surviving Space : Papers on Infant Observation. - Briggs, Andrew (Karnac Books, 2002)
As part of the prestigious Tavistock Clinic Series, this is an essential addition to this highly-valued and innovative series. Infant observation is crucial to most psychotherapy training, and this work would be of obvious value to those commencing their training, as well as valuable insights for all psychotherapists.